(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The aim of this research is to analyze the improvement of speaking skills by using the Peer Group. The researcher carried out in class XI IPA 1 of the SMA SWASTA TAMANSISWA PEMATANG SIANTAR. This research used the quantitative approach with an True experimental design by using Post test only control design by cluster sampling technique. For data collection, there were Pre test and Post test. The technique of collecting the data is by using the statistic application called SPSS 26.00 version. The population of this research 258 students’ in research academic year 2023/2024 with of 34 students’ was the sample. The data analysis was at eleventh grade students stared from scoring pre-test and post- test and finding the different mean of the score. Based on the data analysis, the writer finding pre-test students’ mean score 44,12 and after the treatment, the writer used to post-test to know students’ improve speaking ability score. The result of the test found the average of the pos-test mean score test was 79,71 . The different of the score was significant. It means that using Peer Group in teaching can improve the students’ Speaking skill. So the students’ felt comfortable and enjoyed to learn so that gives a good impact on speaking English skills